Green hospital design: Integrating quality function deployment and end-user demands - Wood, Lincoln; Wang, C.; Abdul-Rahman, H.; Jamal Abdul-Nasir, N. (Elsevier Ltd, 2014)
© 2015 Elsevier Ltd. There is a rapidly growing awareness amongst the public of facilities where the design incorporates green construction principles. This paper aims to study the quality function deployment (QFD) concept and technique when implemented in the construction industry with a particular focus on supporting green hospital design by identifying the end-user factors (concerns) that affect the design. This research develops QFD tools for green hospital designs known as the House of Quality Green Design (HOQGD). Data were collected using a questionnaire survey distributed to public and private hospital end-users in Klang Valley, Malaysia. Findings revealed that end-users perceived "safety mechanisms during emergency" as being of the utmost importance and also the feature they were most satisfied with. The other demanded qualities were at an average degree of satisfaction; however, the end-users considered that green hospital design must make efforts to maximize the use of natural light and ventilation while considering the building orientation; materials should be free from toxicity and be environmentally friendly; the landscape should be strategically designed and the facilities should increase the sense of a healing environment, and water efficient equipment should be installed. Accordingly, these were prioritized and incorporated in the developed HOQGD to inform green hospital design for both public and private facilities.